Identification and characterization of a new variation in DPM2 gene in two Chinese siblings with mild intellectual impairment - Zhao, Peiwei; Hu, Yanqiu; Hu, Juan; Li, Cheng; Huang, Yufeng; Zhang, Lei; Luo, Sukun; Zhu, Hongmin; Jiang, Jun; He, Xuelian (Frontiers in Genetics, 2023)
Congenital disorders of glycosylation (CDGs) are a genetically heterogeneous group of metabolic disorders caused by abnormal protein or lpid glycosylation. DPM2 is one subunit of a heterotrimeric complex for dolichol-phosphate-mannose synthase (DPMS), a key enzyme in glycosylation, and only four patients with DPM2-CDG have been reported. Here we reported two Chinese siblings with a mild form of DPM2-CDG with developmental delay, mild intellectual disability, hypotonia, and increased serum creatine kinase. A homozygous mutation, c.197G>A (p.Gly66Glu) in exon 4 of DPM2 (NM_003863) was identified by whole exome sequencing (WES). In vitro functional analysis demonstrated that this variant increased the expression level of DPM2 protein and western blot revealed a significant decrease in ICAM1, a universal biomarker for hypoglycosylation in patients with CDG, suggesting abnormal N-linked glycosylation. We also reviewed the 4 previously reported patients carrying homozygous or compound heterozygous variants of DMP2 gene, and found that patients with variants within the region encoding the first domain had more severe clinical symptoms than those with variants within the second domain. However, the actual genotype-phenotype relationship needs more study. Overall, our study broadens the variant spectrum of DPM2 gene, attempts to explain the different phenotypes in patients with different DPM2 variants, and emphasizes the need of further functional studies to understand the underlying pathophysiology of the phenotypic heterogeneity.